Новые данные в урартских письмах из Бастама - Арутюнян, H.B. (1988)
Arutjunjan = Harouthyounyan, Nicolai V., New Material from the Urartian Letters of Bastam; Engl. Résumé S.233-236: mLubšuṣini, ḫutuna, ašn(u)-, anagi, ulali